Makna berhadapan dengan notaris pada akta risalah Rapat Umum Pemegang Saham yang diselenggarakan secara elektronik dalam Perspektif Peraturan Perundang-undangan - Yogha Octhanio Pratama; Yetniwati Yetniwati; Dwi Suryahartati (Neolectura, 2022)
This study aims to analyze, find out and then explain the concept of dealing in making the minutes of the General Meeting of Shareholders held electronically. Methods This research uses a normative juridical method. The results of this study are the differences in the views of experts in viewing the expansion of the meaning of